Rapid Memory T-cell Reconstitution Recapitulating CD45RA-depleted Haploidentical Transplant Graft Content in Patients with Hematologic Malignancies - Triplett, Brandon M (Bone Marrow Transplant, 2015)
T-cell depletion of an HLA-haploidentical graft is often used to prevent graft-vs.-host disease (GvHD), but the procedure may lead to increased graft failure, relapse, and infections due to delayed immune recovery. We hypothesized that selective depletion of the CD45RA+ subset can effectively reduce GvHD through removal of naïve T cells, while providing improved donor immune reconstitution through adoptive transfer of CD45RA– memory T cells. Herein, we present results from the first 17 patients with poor-prognosis hematologic malignancy who received haploidentical donor transplantation with CD45RA-depleted progenitor cell grafts following a novel reduced intensity conditioning regimen without total body irradiation or serotherapy. Extensive depletion of CD45RA+ T cells and B cells, with preservation of abundant memory T cells, was consistently achieved in all 17 products. Neutrophil engraftment (median day +10) and full donor chimerism (median day +11) was rapidly achieved post-transplantation. Early T-cell reconstitution directly correlated with the CD45RA-depleted graft content. T-cell function recovered rapidly with broad TCR V(β) spectra. There was no infection-related mortality in this heavily pretreated population, and no patient developed acute GvHD despite infusion of a median of >100 million per kilogram haploidentical T cells.